Knowledge And Attitude Of Integrated Citizens At Ar-Rahman Foundation Towards The Behavior Of Preventing Sexually Transmited Infections - Venny Vildayanti Yulina; Jawiah Jawiah; Rosy Pastuty (Poltekkes Kemenkes Palembang, 2022)
Background: the 2017 Indonesian Demographic and Health Survey noted that 8% of boys and 2% of girls had sexual intercourse. Risky sexual behavior is something that should receive attention, not only because of the long-term impact on reproductive health but most importantly, because of the increase in sexually transmitted infections and the HIV epidemic. Understanding and increasing knowledge about the prevention of sexually transmitted infections is needed to reduce the prevalence of sexually transmitted infections. Objective: to assess the knowledge and attitudes of inmates at the Ar-Rahman drug rehabilitation center towards the behavior of preventing sexually transmitted infections. Methods: this type of research is quantitative analysis with a cross-sectional design. Collecting data by filling out questionnaires to 30 research samples. Bivariate data analysis using the chi-square test (CI=95%). Results: data analysis showed that there was a relationship between knowledge and STI prevention behavior with p=value. 0,003 and there was a relationship between attitude and STI prevention behavior with a p-value=0,033. Conclusion: the level of prevention of STIs will increase if knowledge and attitudes about STIs are good.